The role of apolipoprotein A5 in non-alcoholic fatty liver disease. Issue 7 (21st February 2011) - Ress, C; Moschen, A R; Sausgruber, N; Tschoner, A; Graziadei, I; Weiss, H; Schgoer, W; Ebenbichler, C F; Konrad, R J; Patsch, J R; Tilg, H; Kaser, S
Abstract : Background: Apolipoprotein A5 (apoA5) is a recently described liver-specific protein that has been shown to influence triglyceride (TG) metabolism. ApoA5 transgenic mice display dramatically reduced TG levels, while in contrast apoA5 deficiency in humans was reported to result in marked hypertriglyceridemia. ApoA5 exerts its extracellular effects by increasing lipolysis of TG-rich lipoproteins, while in vitro data suggest additional intrahepatic effects. Methods: In this study the authors set out to investigate a possible role of apoA5 in non-alcoholic fatty liver disease (NAFLD). We thus determined hepatic apoA5 expression in 15 obese subjects with histologically proven NAFLD undergoing bariatric surgery. In addition, the authors established a hepatic cell culture model of apoA5 knockdown by transfecting human hepatoma cells (HepG2) with apoA5 small interfering (si) RNA, and determined intracellular TG content and expression levels of key enzymes and transcription factors of intrahepatic lipid metabolism in these cells. Results: Pronounced weight loss and associated histologically verified improvement of hepatic steatosis were accompanied by significant reductions of hepatic apoA5 mRNA expression levels. Significant apoA5 knockdown in HepG2 cells resulted in a marked decrease of intracellular TG content. When HepG2 cells were co-transfected with apoA5 and peroxisome proliferator-activated receptor gamma (PPARγ), reductions in hepatic TG accumulation were significantly less pronounced when compared to apoA5 siRNA transfected HepG2 cells. Conclusions: In obese subjects, hepatic apoA5 mRNA expression decreases after weight loss and improvements in hepatic steatosis. The authors' in vitro data demonstrate that apoA5 influences intrahepatic TG metabolism and that these intracellular effects of apoA5 are accompanied by changes in PPARγ mRNA expression. In summary, the data suggest that as well as several other factors, apoA5 might be involved in the pathogenesis of hepatic steatosis.